2015
DOI: 10.3109/00498254.2015.1048327
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory effects and oxidation of 6-methylcoumarin, 7-methylcoumarin and 7-formylcoumarinviahuman CYP2A6 and its mouse and pig orthologous enzymes

Abstract: 1. Information about the metabolism of compounds is essential in drug discovery and development, risk assessment of chemicals and further development of predictive methods. 2. In vitro and in silico methods were applied to evaluate the metabolic and inhibitory properties of 6-methylcoumarin, 7-methylcoumarin and 7-formylcoumarin with human CYP2A6, mouse CYP2A5 and pig CYP2A19. 3. 6-Methylcoumarin was oxidized to fluorescent 7-hydroxy-6-methylcoumarin by CYP2A6 (Km: 0.64-0.91 µM; Vmax: 0.81-0.89 min(-1)) and by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 47 publications
2
14
0
Order By: Relevance
“…Altogether, the stability, the distance of the closest carbon to the heme iron, and the binding energy estimations suggested that the primary SOM in 6-methylcoumarin would be C7 in pose 1 (Tables 1 and 2). This result, where C7 is the preferred SOM, correlates with the experimental results, which show that the primary metabolite is hydroxylated at C7 (Juvonen et al, 2016).…”
Section: -Methylcoumarinsupporting
confidence: 88%
See 2 more Smart Citations
“…Altogether, the stability, the distance of the closest carbon to the heme iron, and the binding energy estimations suggested that the primary SOM in 6-methylcoumarin would be C7 in pose 1 (Tables 1 and 2). This result, where C7 is the preferred SOM, correlates with the experimental results, which show that the primary metabolite is hydroxylated at C7 (Juvonen et al, 2016).…”
Section: -Methylcoumarinsupporting
confidence: 88%
“…For CYP2A6, two known substrates, coumarin and 6-methylcoumarin, were selected. Both compounds are 7-hydroxylated in CYP2A6 oxidation (Juvonen et al, 2016;Pelkonen, Rautio, Raunio, & Pasanen, 2000). For AR, ligands were separated from the chosen protein crystal structures.…”
Section: Ligand Preparationmentioning
confidence: 99%
See 1 more Smart Citation
“…The five chemicals for which the metabolites did not correlate with reported information were: 6‐methylcoumarin, dimethyl phthalate; nitrobenzene; geraniol and Basic Red 76. For 6‐methylcoumarin, the literature value was for liver microsomes supplemented with NADPH (Juvonen et al, ), which only represents Phase 1 reactions and would not produce the glucuronide detected in these S9 incubations. Although dimethyl phthalate was rapidly metabolized by both liver and EpiSkin S9, there were no metabolites detected, possibly due to the analytical conditions being optimal for the parent and not the metabolites.…”
Section: Discussionmentioning
confidence: 99%
“…Published information on the in vivo and/or in vitro metabolism was available for 35 of the chemicals tested, which was used to assess whether the liver and/or EpiSkin S9 produced relevant metabolites ( (Juvonen et al, 2016), which only represents Phase 1 reactions and would not produce the glucuronide detected in these S9 incubations.…”
Section: Discussionmentioning
confidence: 99%